Disaster Preparedness of High School Students in Red Zone and Green Zone - Emil Huriani; Adliah Wulan Sari; Tiurmaida Simandalahi (Fakultas Keperawatan Universitas Andalas, 2025)
Background; Disaster mitigation was focused on the red zone that making kind of differences in students’ preparedness levels between the red zone and green zone. Meanwhile, Padang City has the potential for a Megathrust earthquake of 8.9 SR. This research aimed to determine the comparison in earthquake and tsunami disaster preparedness levels of high school students in the red and green zones Methods: This research was a descriptive comparative study. The sampling technique used the cluster random sampling method as many as 139 high school students from the red zone and 136 high school students from the green zone. The research instrument used preparedness questionnaire from LIPI/UNESCO/ISDR. Results: The results of this study showed that there were significant differences in preparedness (p<0,001) as well as another parameter namely knowledge (p=0.030), emergency planning (p<0,001), early warning systems (p<0,001), and resource mobilization capacity (p=0.015) between high school students in the red zone and the green zone. Conclusion: It is hoped that schools can complete risk maps, evacuation routes, gathering points, create preparedness guidelines and hold disaster management simulation activities for students. The nursing profession can participate in disaster risk education and campaign for disaster preparedness bags in an effort to increase student preparedness in all vulnerability zones.